TANBĪH AL-MĀSYI AL-MANSŪB ILĀ TARĪQ AL-QUSYASYĪ: Analisis Uslub Bahasa Arab dalam Karya ‘Abd Ar-Rauf As-Singkili - Rasyad Rasyad; Hermansyah Hermansyah; Zulkhairi Zulkhairi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
'Abd ar-Rauf al-Jawi al-Fansuri As-Singkili is a prolific scholar. He authored dozens of books in various fields and a variety of topics. Among his work written entirely in Arabic is al-MÄsyÄ« Tanbih al-MansÅ«b Tariq ila al-QusyÄshy. The text discusses the mysticism and monotheism, written around 1661 in Aceh. The text contains three forms of uslub, namely; uslub 'ilmi, uslub khitabi and uslub adabi. Uslub 'ilmi is more dominant in usage and more influential in the style of his thinking and writing than uslub khitabi adabi. There are lafadz tasybÄ«h, iqtibÄs, amr, nidaâ€™, tawkÄ«d, and others can be found in the three elements of uslub. The meaning of the uslub sentence itself depends on the context